=====================================================
Explanation:
Let a and b take on scalar values.
v = au + bw
v = a(2,1) + b(2,-3)
v = (2a, 1a) + (2b, -3b)
v = (2a+2b, 1a-3b)
Set this equal to (4, -2) and equate components
(2a+2b, 1a-3b) = (4, -2)
2a+2b = 4 and 1a-3b = -2
We have this system of equations
[tex]\begin{cases}2a+2b = 4\\1a-3b = -2\end{cases}[/tex]
Multiply everything in the second equation by -2
So we go from 1a-3b = -2 to -2a+6b = 4
We have this equivalent system of equations
[tex]\begin{cases}2a+2b = 4\\-2a+6b = 4\end{cases}[/tex]
Add straight down
We then have 8b = 8 which solves to b = 1
Use this to find 'a'
2a+2b = 4
2a+2(1) = 4
2a+2 = 4
2a = 4-2
2a = 2
a = 2/2
a = 1
We found that a = 1 and b = 1
Therefore,
v = au + bw
v = 1u + 1w
v = u + w
v = 1*(2,1) + 1*(2,-3)
v = (1*2, 1*1) + (1*2, 1*(-3))
v = (2, 1) + (2, -3)
v = (2+2, 1-3)
v = (4, -2)
which confirms the answer.